(untitled) (Medico Legal Update, 2021)
The life style of the people by large has been adversely affected due to manifold reasons which includes industrialization and eventually making obesity as a very fast growing epidemic worldwide. Consequence of overweight, results in chronic diseases like cardiovascular issues, diabetes, and cancer. Nearly every obese person is found to be hyperlipidemia, which indicates a condition of having high levels of cholesterol, cholesterol esters, triglycerides, low-density lipoprotein and depleted levels of high-density lipoprotein. The high frequency of side effects implications of the drugs available in the market has raised a dire need of discovering and developing a new novel drug. The studies show that the plants have proven to be an upright source of natural as well as multifunctional molecules. The natural molecules flavonoids along with other components have been reported for multi-functionality. HyphaeneThebaica and NelumboNucifera have direct lowering effect on blood lipids and hypertension. This review explains the effect of HyphaeneThebaica (Doum) and NelumboNucifera (Lotus seeds) on blood lipids and hypertension. Lipid profile will be evaluated by estimation of Cholesterol count , Triglycerides , High and low density lipoprotein while hypertension will be evaluated by measuring Aginotensin converting enzyme ( ACE) in serum and tissue extraction. Herbal medicine is the new good treatment for many chronic diseases to get ride from side effects of anticholestremic and anti-hypertension drugs.